2013
DOI: 10.3892/ijo.2013.1827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voluntary exercise on tumorigenesis in the C3(1)/SV40Tag transgenic mouse model of breast cancer

Abstract: Abstract. Epidemiologic studies suggest an association between physical activity (PA) and breast cancer risk. We examined the relationship between voluntary wheel running and breast cancer in C3(1)/SV40Tag mice. Female FVB/N and C3(1)/SV40Tag mice were assigned to either PA [C3(1)-PA] (n=12) or sedentary (Sed) [C3(1)-Sed] (n=15) treatment and were placed in a cage with access to a running wheel (PA) or without (Sed) from 4 to 24 weeks of age (sacrifice). Physical activity data were analyzed for running distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…; Steiner et al . ). However, some studies failed to demonstrate any beneficial effects of physical training on tumour development and progression (Jones et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Steiner et al . ). However, some studies failed to demonstrate any beneficial effects of physical training on tumour development and progression (Jones et al .…”
Section: Discussionmentioning
confidence: 97%
“…One issue with caliper measurements is that these measurements are typically used to generalize the tumor volume from measurements in only two dimensions with the equation [0.5× (largest diameter) × (smallest diameter) 2 ] [18], [19]. While tumors can sometimes be measured with calipers in three dimensions for a more accurate estimate of the tumor size [20], the orthotopic tumors in our study were often too small, especially in the MMAE-treated group, to obtain an accurate, consistent measurement of their heights through the mammary fat pads.…”
Section: Discussionmentioning
confidence: 99%
“…Steiner et al demonstrated that voluntary wheel running reduced the mean tumor volume, although this activity was associated with an increased number of tumors developing in mice. 41 On the contrary, Whittal-Strange et al found an increase in tumor weight under the influence of physical training, especially in the course of high-intensity exercise. 18 These findings indicate that the risk of breast cancer development increases as a consequence of physical exercise, therefore pointing to its negative impact in cancer patients.…”
mentioning
confidence: 96%